Hubungan Kualitas Pelayanan Kesehatan dengan Biaya Total Pasien Apendektomi Terbuka di Rumah Sakit Tipe C dengan Cakupan Asuransi Kesehatan di Indonesia (BPJS Kesehatan): Penelitian - Siahaan, Ayesha Melissa Rahmania; Ugut, Gracia Shinta Setyadi (PT Kalbe Farma Tbk., 2026)
Introduction: Under BPJS Health, both open and laparoscopic appendectomies, are reimbursed at the same rate despite differences in consumable use. This study aimed to investigate whether open appendectomy provides favorable clinical outcomes at a lower cost and to analyze healthcare costs and service quality in class C private hospitals. Methods: This quantitative study was conducted at a type C hospital in South Jakarta from January 2022 to August 2023. The sample size was calculated using G*Power, the minimum required sample was 70 patients, based on linear multiple regression analysis. Patients included were those with appendicitis undergoing appendectomy under BPJS Kesehatan coverage, selected through purposive sampling. Patients with upgraded insurance or laparoscopic surgery were excluded. Data from medical records were analyzed using logistic regression with a significance level of p < 0.05. Results: Postoperative infection after appendectomy does not significantly influence cost and quality of care, possibly due to other factors. However, length of stay does, as longerpatients require more resources. Cost significantly influences quality of care (p < 0.05). Conclusion: Postoperative infections do not significantlyimpact care costs, suggesting case-mix and illness severity are more influential. Longer stays result in higher costs, especially in advanced services. Hospital management should prioritize controlling complications and infections to improve service and meet accreditation standards.